Survivors of the Shoah: Interviewee: C. Sebestyen Part I (Survivors of the Shoah Visual History Foundation, 1996)
Shoah Foundation interview code: 13576 Duration: 02:02:00 Interview with Hungarian Holocaust survivor C. Sebestyen. The tape is part of a collection of 10 interviews provided to OSA by the Survivors of the Shoah Visual History Foundation. Interviewer: Paula Saltman.